2006
DOI: 10.1128/cvi.13.4.475-485.2006
|View full text |Cite
|
Sign up to set email alerts
|

High Titers of Circulating Maternal Antibodies Suppress Effector and Memory B-Cell Responses Induced by an Attenuated Rotavirus Priming and Rotavirus-Like Particle-Immunostimulating Complex Boosting Vaccine Regimen

Abstract: Vaccination of neonates faces many challenges due to the immaturity of the neonatal immune system and interference by maternal antibodies (MatAbs) present at vaccination. Various degrees of interference of vaccine-induced immune responses by MatAbs have been reported for live vaccines such as measles and Sabin oral poliomyelitis vaccines as well as for nonreplicating vaccines (i.e., inactivated or subunit vaccines) such as tetanus, diphtheria, Haemophilus influenzae, hepatitis A and B, classical swine fever vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…2A). However, this may have been due to the inhibitory effect of high levels of circulating antibodies, after the single immunization, on the booster effect in the 5-g HA-immunized mice, since such a negative-feedback inhibitory effect of antibodies has been noted previously (28). We further compared the dose-sparing efficacy of RIG-I pathway activation with TLR4, TLR7, and alum (NLR) pathway activation in inducing recall memory antibody responses when a sparing dose of 0.5-g HA vaccine was used.…”
Section: Resultsmentioning
confidence: 90%
“…2A). However, this may have been due to the inhibitory effect of high levels of circulating antibodies, after the single immunization, on the booster effect in the 5-g HA-immunized mice, since such a negative-feedback inhibitory effect of antibodies has been noted previously (28). We further compared the dose-sparing efficacy of RIG-I pathway activation with TLR4, TLR7, and alum (NLR) pathway activation in inducing recall memory antibody responses when a sparing dose of 0.5-g HA vaccine was used.…”
Section: Resultsmentioning
confidence: 90%
“…Since this study did not include colostrum-deprived piglets, this question remains open. It is noteworthy that other studies have observed a good immune response in suckling piglets with vaccines against other pathogens and have demonstrated that maternal antibodies reduced the impact of vaccination in swine (17).…”
Section: Discussionmentioning
confidence: 93%
“…The protective efficacies of the different S. suis vaccination regimes are unknown, since comparative evaluations have not been described. Maternal antibodies might exhibit positive or negative effects of various degrees on vaccine-induced immune responses in progeny, as has been shown for different pathogens (17,18). The working hypothesis of this study was that S. suis immunization of preparturient sows might elicit protective passive maternal immunity but might also influence active immunization of piglets.…”
mentioning
confidence: 76%
“…The blocking effects of maternal antibodies have been demonstrated for both enteric and respiratory vaccines, such as RV (37)(38)(39), swine influenza (40,41), bovine respiratory syncytial virus (42), and bovine viral diarrhea virus (43)(44)(45). These studies have suggested that for live vaccines, the presence of maternal antibodies may result in low rates of seroconversion.…”
Section: Suppressive Effects Of Maternal (Passive) Antibodies On Immumentioning
confidence: 99%